RELATIONSHIP BETWEEN SERUM LEVEL OF IONIZED CALCIUM, MAGNESIUM, PHOSPHATE, VITAMIN D AND PARATHYROID HORMONE WITH STAGES OF CKD - Mohammed A (Ntec Specialist, 2020)
Background: Chronic kidney disease is defined as either damage or a decreased Glomerular Filtration Rate of less than 60ml/min/1.73m2 for 3 or more months. There is destruction of renal mass with irreversible sclerosis and loss of nephron leading to a progressive decline in GFR.Secondary hyperparathyroidism, hyperphosphataemia, hypocalcaemia and vitamin-D deficiency are common complications of CKD. Objective: To determine relationship between serum level of ionised calcium, magnesium, phosphate, vitamin-D and parathyroid hormone with stages of CKD. Method: This study was conducted at ABUTH Zaria. 125 consecutive adult patients in various stages of CKD who presented were enrolled and 125 apparently healthy matched for sex and age controls were also recruited. Results: 9% of patients were in stage-1, 16% in stage-2, 22% in stage-3, 12% in stage-4 and 41% in stage-5. Serum ionised calcium, vitamin-D and eCrCl showed a progressive decline as the stage of CKD advances, while serum phosphate, creatinine and iPTH showed a progressive increase as the stage of CKD advances. Changes in serum magnesium showed a slight change with advancing stages of CKD. The difference in mean serum levels of calcium, phosphorus, vitamin-D, parathyroid hormone, creatinine and eCrCl with different stages of CKD were statistically significant. eCrCl correlated negatively with phosphate and iPTH while serum creatinine correlated negatively with calcium and positively with phosphate and iPTH. Conclusion: Majority of CKD patients were in late stage. Correlation of analytes with stages was more in late stages and biochemical derangements occurred in late, rather than early stages of CKD